Relayed Regioselective Alkynylation/Olefination of Unsymmetrical Cyclic Diaryliodonium Species Catalyzed by Cu and Pd: Affording Fluorescent Cytotoxic Benzoxazoles. Issue 52 (24th November 2015) - Zhu, Daqian; Liu, Panpan; Lu, Wenhua; Wang, Haiwen; Luo, Bingling; Hu, Yumin; Huang, Peng; Wen, Shijun
Abstract: Although cyclic diaryliodonium species have the potential to act as valuable synthons for cascade transformations, they still remain largely unexplored. The regioselectivity associated with unsymmetrical cyclic diaryliodonium species has previously been known to pose a challenge. A regioselective relayed alkynylation and olefination of unsymmetrical cyclic diaryliodonium species has been achieved by installation of a directing amido group. These relayed transformations were delayed until an oxazole ring had formed, delivering a series of unique fluorescent benzoxazoles. Moreover, some of these synthetic benzoxazoles showed apparent inhibitory activity against malignant cancer cells. Further confocal visualization revealed that benzoxazoles targeted cell nuclei. These findings might provide a novel structural scaffold to develop desirable anticancer agents. Abstract : Dual is good : Mediated by dual transition metal catalysts, Cu and Pd, amido groups in unsymmetrical cyclic diaryliodonium species dictate the order of reaction transformations. The resultant novel benzoxazole products exhibit unique structural features, fluorescence, and anticancer activity, enabling the tracking of a subcellular target.